Effect of Different Multivitamins on Growth Performance and Survival of Depik Fish (Rasbora tawarensis Weber & de Beaufort, 1916) - Iwan Hasri; Mu'amar Abdan; Lizawati Putri; Rizkan Fahmi; Zulida Susanti; Fita Rhidana (Journal of Aquaculture and Fish Health, 2023)
Depik Fish (Rasbora tawarensis) is an endemic fish species found in Tawar Lake, with a threatened status. Domestication efforts are being undertaken to conserve the Depik Fish population. This study aimed to analyze the effectiveness of different vitamins on the growth and survival of Depik Fish. The study was conducted at Balai Benih Ikan (BBI), Pegasing - Central Aceh Regency, from December 2021 to January 2022. A Complete Random Design (CRD) with four treatment levels and four replications was employed, including a control group and three experimental groups: 300 mg/kg feed of vitamin C, vitamin B complex, and Viterna Plus. The results of the Anova test indicate that the dosage of vitamin C, vitamin B complex, and Viterna Plus in commercial feed significantly influenced the absolute weight growth, absolute length growth, and specific growth rates of the Depik Fish (P<0.05). However, it did not have a significant effect on feed efficiency and survival. Duncan’s test revealed significant differences among the treatment groups, with the highest values observed in the application of Viterna Plus at a dosage of 300 mg/kg feed, which resulted in increased growth and survival of the Depik Fish. Therefore, the use of Viterna Plus in fish feed is recommended.